(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Abstract This article examines South Korea’s public Recognition of Prior Learning (RPL) practices for North Korean refugees, focusing on how learning is recognized when official educational documentation is missing, incomplete, or not transferable. Kang and Lee situate the issue within broader patterns of forced displacement and analyze the academic recognition system centered on the Academic Background Deliberative Committee. They show how administrative records, oral interviews, and written assessments are combined to evaluate prior learning and determine educational placement. The article highlights both the flexibility and the limits of this approach, including regional inconsistencies, the enduring authority of state-generated documents, and the lack of comparable recognition mechanisms in higher education. Keywords: Recognition of Prior Learning (RPL); North Korean refugees; undocumented learning; academic recognition; forced displacement; public policy; alternative assessment; South Korea